#### Answer

This equation has no solution

#### Work Step by Step

$-2(x-5)+10=-3(x+2)+x$
Solving that, we have:
$-2x+10+10=-3x-6+x$
$-2x+20=-2x-6$
$-2x+2x=-6-20$
$0=-26$
This equation has no solution

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

This equation has no solution

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.